Benthic Oxygen and Nitrogen Exchange on a Cold-Water Coral Reef in the North-East Atlantic Ocean - de Froe, Evert; Rovelli, Lorenzo; Glud, Ronnie N.; Maier, Sandra R.; Duineveld, Gerard; Mienis, Furu; Lavaleye, Marc; van Oevelen, Dick (Frontiers in Marine Science, 2019)
Cold-water coral (CWC) reefs are distributed globally and form complex three-dimensional structures on the deep seafloor, providing habitat for numerous species. Here, we measured the community O2 and dissolved inorganic nitrogen (DIN) flux of CWC reef habitats with different coral cover and bare sediment (acting as reference site) in the Logachev Mound area (NE Atlantic). Two methodologies were applied: the non-invasive in situ aquatic eddy co-variance (AEC) technique, and ex situ whole box core (BC) incubations. The AEC system was deployed twice per coral mound (69 h in total), providing an integral estimate of the O2 flux from a total reef area of up to 500 m2, with mean O2 consumption rates ranging from 11.6 ± 3.9 to 45.3 ± 11.7 mmol O2 m-2 d-1 (mean ± SE). CWC reef community O2 fluxes obtained from the BC incubations ranged from 5.7 ± 0.3 to 28.4 ± 2.4 mmol O2 m-2 d-1 (mean ± SD) while the O2 flux measured by BC incubations on the bare sediment reference site reported 1.9 ± 1.3 mmol O2 m-2 d-1 (mean ± SD). Overall, O2 fluxes measured with AEC and BC showed reasonable agreement, except for one station with high habitat heterogeneity. Our results suggest O2 fluxes of CWC reef communities in the North East Atlantic are around five times higher than of sediments from comparable depths and living CWCs are driving the increased metabolism. DIN flux measurements by the BC incubations also revealed around two times higher DIN fluxes at the CWC reef (1.17 ± 0.87 mmol DIN m-2 d-1), compared to the bare sediment reference site (0.49 ± 0.32 mmol DIN m-2 d-1), due to intensified benthic release of NH4+. Our data indicate that the amount of living corals and dead coral framework largely contributes to the observed variability in O2 fluxes on CWC reefs. A conservative estimate, based on the measured O2 and DIN fluxes, indicates that CWC reefs process 20% to 35% of the total benthic respiration on the southeasterly Rockall Bank area, which demonstrates that CWC reefs are important to carbon and nitrogen mineralization at the habitat scale.